Pre-regulation of the planar chirality of pillar[5]arenes for preparing discrete chiral nanotubes. Issue 10 (8th February 2021) - Fa, Shixin; Adachi, Keisuke; Nagata, Yuuya; Egami, Kouichi; Kato, Kenichi; Ogoshi, Tomoki
Abstract : Pillar[5]arene-based chiral nanotube formation via pre-regulation of the building blocks' chirality is more efficient than post-regulating the chirality of nanotubes. Abstract : Regulating the chirality of macrocyclic host molecules and supramolecular assemblies is crucial because chirality often plays a role in governing the properties of these systems. Herein, we describe pillar[5]arene-based chiral nanotube formation via pre-regulation of the building blocks' chirality, which is different from frequently used post-regulation strategies. The planar chirality of rim-differentiated pillar[5]arenes is initially regulated by chiral awakening and further induction/inversion through stepwise achiral external stimuli. The pre-regulated chiral information is well stored in discrete nanotubes by interacting with a per-alkylamino-substituted pillar[5]arene. Such pre-regulation is more efficient than post-regulating the chirality of nanotubes.